Salivary cortisol and immunoglobulin A responses during golf competition vs. practice in elite male and female junior golfers - Kim, K. J.; Park, S.; Kim, K. H.; Jun, T. W.; Park, D. H.; Kim, K. B. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate the stress and immune responses to a competition in elite male and female junior golfers. Six male (16.2 ± 1.4 years) and 6 female junior golfers (16.4 ± 1.1 years) completed salivary collections during competition vs. practice rounds on 2 different days. Salivary samples were collected on 4 occasions (rest, before, during, and after rounds). Salivary cortisol and IgA were measured for stress and immune responses, respectively. Our results were as follows: (a) Salivary cortisol level was higher in competition than practice in male golfers (p = 0.009) but it was similar in female golfers. In male golfers, salivary cortisol level was higher before a round than at rest (p = 0.029), but it was higher after rounds than at rest (p = 0.016) in female golfers. (b) Salivary IgA was elevated during competition than during practice rounds in male golfers (p = 0.019), but not in females (p = 0.152). Salivary IgA was not significantly different among salivary collection times although it tended to be elevated during and after rounds for both male and female golfers. In conclusion, salivary cortisol and IgA were elevated during golf competition compared with practice in male junior golfers, but they were not in female golfers. Furthermore, salivary cortisol was higher before a round than rest in men, but it was higher after a round than rest in women. Both male and female junior golfers, however, showed similar salivary IgA responses during golf. Our results suggest that sex might play a role on stress and immune responses during a game of golf in elite junior golfers.